Nullius in Verba: A call for the incorporation of evidence-based practice into the discipline of exercise science - Amonette, W. E.; English, K. L.; Ottenbacher, K. J. (Sports Medicine, 2010)
Evidence-based practice (EBP) is a concept that was popularized in the early 1990s by several physicians who recognized that medical practice should be based on the best and most current available evidence. Although this concept seems self-evident, much of medical practice was based on outdated textbooks and oral tradition passed down in medical school. Currently, exercise science is in a similar situation. Due to a lack of regulation within the exercise community, the discipline of exercise science is particularly prone to bias and misinformation, as evidenced by the plethora of available programmes with efficacy supported by anecdote alone. In this review, we provide a description of the five steps in EBP: (i) develop a question; (ii) find evidence; (iii) evaluate the evidence; (iv) incorporate evidence into practice; and (v) re-evaluate the evidence. Although objections have been raised to the EBP process, we believe that its incorporation into exercise science will improve the credibility of our discipline and will keep exercise practitioners and academics on the cutting edge of the most current research findings.